2014
DOI: 10.1111/crj.12050
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease as comorbidity in patients admitted to a university hospital: a cross‐sectional study

Abstract: Seventy-seven per cent of the COPD patients in this study were newly diagnosed at our examination. Gastrointestinal diseases, haematologic diseases and uro-nephrologic diseases were significantly more prevalent in COPD patients. COPD patients were hospitalised significantly longer than non-COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…These studies have found between 25 and 34% of the study populations to have undiagnosed COPD. [9,16] This is not consistent with the findings of this study where a considerably smaller proportion the examined patients were diagnosed with COPD. There are several possible explanations of this.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…These studies have found between 25 and 34% of the study populations to have undiagnosed COPD. [9,16] This is not consistent with the findings of this study where a considerably smaller proportion the examined patients were diagnosed with COPD. There are several possible explanations of this.…”
Section: Discussioncontrasting
confidence: 94%
“…There are several possible explanations of this. In the study by Kart et al [16] examining outpatients and patients hospitalized for elective treatment, a considerably larger proportion of the study population were able to participate in spirometry; in the study by Nielsen et al [9] all inpatients were examined, and in neither of these studies the study populations were followed up in stable state. In fact, in this study a larger proportion of the study population had airflow obstruction at the initial examination than in the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third, more modest, study of 215 patients admitted to hospital (28% diagnosed with COPD) observed no differences in the number of multimorbidities between patients with and without COPD. However, gastrointestinal, haematological and uro-nephrological disorders were more prevalent in patients with COPD and their hospital stay was longer [3]. Finally, a landmark study of the role played by multimorbidities in systemic inflammation in 213 patients with COPD, after excluding active inflammatory disease, did not make any reference to IBD or hepatic diseases [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing clinical interest in secondary organ manifestations of chronic respiratory diseases and respiratory viral infections are often accompanied by intestinal symptoms [2][3][4][5][6] . Gastro-intestinal (GI) disease is more prevalent in patients with chronic obstructive pulmonary disease (COPD) than in healthy populations 7,8 . A population-based cohort showed a 2.72 times higher risk of Crohn's disease in COPD sufferers than that in healthy controls 9 .…”
Section: Introductionmentioning
confidence: 99%